Mathematics Learning Based on Traditional Bomboman Games as an Effort to Develop Strategic Mathematical Abilities - Fajrin, Afan; Arzaqi, Argha Zidan (STAI Miftahul Ula Nganjuk, 2025)
This study aims to design and test mathematics learning based on the traditional bomboman game as an effort to develop students' strategic mathematical competence. This research consists of three stages, namely: identification and analysis of traditional games, design of traditional game-based learning based on Realistic Mathematics Education (RME), and implementation in classroom learning involving 34 grade 8 students. Data related to traditional games was collected through observation and interviews with the residents where the game originated. Data on students' strategic mathematical abilities were obtained through tests given after learning. Analysis of student test results refers to indicators of students' strategic mathematical competency. The results showed that 20 students succeeded in fulfilling all indicators of strategic mathematical competence with a very good final grade category. While 14 students succeeded in achieving the first indicator (formulating the problem) but not all of them fulfilled the indicator of representing and solving the problem. The findings of this study indicate that learning mathematics based on the traditional Bomboman game has the potential to help students develop mathematical strategic abilities.